The promise of the suburbs : a Victorian history in literature and culture - Bilston, Sarah (Yale scholarship online, 2019)
A study of the fast-growing Victorian suburbs as places of connection, creativity, and professional advance, especially for women. From the earliest decades of the nineteenth century, the suburbs were maligned by the aristocratic elite as dull zones of low cultural ambition and vulgarity, as well as generally female spaces isolated from the consequential male world of commerce. Sarah Bilston argues that these attitudes were forged to undermine the cultural authority of the emerging middle class and to reinforce patriarchy by trivializing women's work. Resisting these stereotypes, Bilston reveals how suburban life offered ambitious women, especially women writers, access to supportive communities and opportunities for literary and artistic experimentation as well as professional advancement. From more familiar figures such as the sensation author Mary Elizabeth Braddon to interior design journalist Jane Ellen Panton and garden writer Jane Loudon, this work presents a more complicated portrait of how women and English society at large navigated a fast-growing, rapidly changing landscape.